Pengaruh Fraud Diamond Terhadap Perilaku Kecurangan Akademik Mahasiswa dengan Dua Faktor Moderasi - Hidayah, Nila; Sholiqin, M. Nur (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2022)
The purpose of this study is to identify and analyze the factors that influence student fraud at the academic level in the Accounting Study Program, where in the main scope of education students are expected to become anti-fraud generations, so it needs to be instilled since they were in college, considering that based on previous research not a few students who have committed acts of academic fraud. Factors of academic fraud behavior include pressure, opportunity, rationalization and capability called fraud diamond which needs to be explored more deeply to test the effectiveness of the fraud concept, as well as two moderating factors, namely gender and religiosity. This research is a type of quantitative research and literacy studies. The results of the study can be concluded that the opportunity and capability factors have a significant influence while the factors of pressure, rationalization, gender and religiosity have an insignificant effect on student academic fraud behavior.